(1S,3R,8R)-2,2-Dibromo-3,7,7,10-tetramethyltricyclo[6.4.0.0(1,3)]dodec-9-ene - Benharref, Ahmed (International Union of Crystallography, 2012)
The title compound, C(16)H(24)Br(2), was synthesized from β-himachalene (3,5,5,9-tetramethyl-2,4a,5,6,7,8-hexahydro-1H-benzocycloheptene), which was isolated from the essential oil of the Atlas cedar (Cedrus Atlantica). The molecule is built up from two fused six- and seven-membered rings and an additional three-membered ring from the reaction of β-himachalene with dibromocarbene. The six-membered ring shows a screw-boat conformation, whereas the seven-membered ring displays a boat conformation; the dihedral angle between the mean planes through the rings is 57.9 (4)°. The absolute structure was established unambiguously from anomalous dispersion effects.